Multinational Business Finance / Third Edition - Eiteman David K; Stonehill Arthur I (Addison-Wesley Publishing Company, 1982)
The Multinational Corporation and Its International Environment, Foreign Exchange Risk Management, Long-Run Investment Decisions, Financing Decisions, Working Capital Management, Control.